BUDIDAYA ULAT SUTERA DAN PRODUKSI BENANG SUTERA MELALUI SISTEM KEMITRAAN PADA PENGUSAHAAN SUTERA ALAM (PSA) REGALOH KABUPATEN PATI - Eka Dewi Nurjayanti (MEDIAGRO, 2011)
This study aimed to determine  the process of cultivation and silkworm silk yarn production in the Exploitation of Natural Silk (PSA) Pati Regaloh. The basic method  of research used  is descriptive method. Determining the  location of  the research conducted (purposive), the Concession Alam Sutera (PSA) Regaloh. The results  obtained are  Regaloh  PSA  has implemented a  system of  partnerships between employers and  the surrounding  farming community  through  the core system and plasma. Technically maintenance silkworms can be divided  into two, namely  the maintenance  of mulberry  plantation  and  silkworm  breeding.  The species  planted mulberry  is Morus multicaulis Regaloh  PSA, Morus  cathayana, Morus nigra, Morus alba and mulberry mixed types. Mulberry plant maintenance includes  fertilizing, pendangiran  (weeding),  and  trimming. Maintenance  consists of maintenance silkworm caterpillars are small and  large caterpillars. Harvesting is done after the silkworm cocoon mengokon for 6-7 days in the maintenance brak brak-large  caterpillar.  The processing of  cocoons  into  silk yarn  is divided  into several stages, namely boiling, reeling, rereeling, pressing and packing.   Keywords: cultivation of silkworms, silk yarn, partnership, PSA Regaloh